Cardiac resident macrophages: Spatiotemporal distribution, development, physiological functions, and their translational potential on cardiac diseases - Jin, Jing; Wang, Yurou; Liu, Yueqin; Chakrabarti, Subrata; Su, Zhaoliang (Acta pharmaceutica Sinica. B, 2024)
Cardiac resident macrophages (CRMs) are the main population of cardiac immune cells. The role of these cells in regeneration, functional remodeling, and repair after cardiac injury is always the focus of research. However, in recent years, their dynamic changes and contributions in physiological states have a significant attention. CRMs have specific phenotypes and functions in different cardiac chambers or locations of the heart and at different stages. They further show specific differentiation and development processes. The present review will summarize the new progress about the spatiotemporal distribution, potential developmental regulation, and their roles in cardiac development and aging as well as the translational potential of CRMs on cardiac diseases. Of course, the research tools for CRMs, their respective advantages and disadvantages, and key issues on CRMs will further be discussed. CRM subsets reside in different anatomical niches with high spatiotemporal heterogeneity and play different roles in cardiac development and pathophysiology. [Display omitted]